Influence of kinesiophobia and pain catastrophism on objective function in women with patellofemoral pain - Priore, Liliam B. [UNESP]; Azevedo, Fábio M. [UNESP]; Pazzinatto, Marcella F. [UNESP]; Ferreira, Amanda S. [UNESP]; Hart, Harvi F.; Barton, Christian; de Oliveira Silva, Danilo [UNESP] (Elsevier, 2019)
Objectives: (i) To compare kinesiophobia, pain catastrophism and objective function between women with patellofemoral pain (PFP) and pain-free; (ii) to investigate the association of kinesiophobia and pain catastrophism with objetive function in women with PFP. Design: Case-control. Setting: Laboratory-based. Participants: Fifty-five women with PFP and forty pain-free women. Main outcome measures: Kinesiophobia and pain catastrophism were assessed using the Tampa Scale of Kinesiophobia and Pain Catastrophizing Scale, respectively. Forward step-down, single leg hop, and modified star balance tests were used to assess objective function. Independent t-tests were used for between-groups comparisons and Pearson correlation coefficients were used to investigate the association between the outcomes. Results: Women with PFP had significantly worse kinesiophobia (p < 0.001; Effect size (ES) = 1.16), pain catastrophism (p < 0.001; ES = 1.57), and poorer objective function (step-down, (p < 0.001; ES = 0.99); single-leg hop (p = 0.002; ES = 0.74); modified star balance (p < 0.001; ES = 0.66) than pain-free controls. Kinesiophobia and pain catastrophism were not correlated with objective function. Conclusion: Greater kinesiophobia, pain catastrophism and poorer objective function is evident in women with PFP, compared to pain-free controls. Kinesiophobia and pain catastrophism were not associated with objective function in women with PFP. Future research is necessary to understand how other physical and psychological factors might affect objective function.
Keywords: Anterior knee pain; Pain; Psychologic; psychological factors